Bahasa dan Identitas dalam Ketepik Bulian Padi yang Dilantunkan dalam Gambus Belitung: Sebuah Kajian Sosiolinguistik - Aimie Sulaiman; Nurvita Wijayanti; Andri Fernanda (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Gambus and song lyrics complement each other, creating harmony while representing the history and cultural identity of their communities. This study aims to explore identity through diction choices, phonological processes, and musical notes in Gambus. These elements are assumed to reflect social relations and cultural identity. The sociolinguistic theory of isolect and identity theory are applied to analyze the lyrics and musical notes. This qualitative descriptive study employs library research using the song lyrics of Ketepik Belian Padi and the Gambus melody played by Sukino (a Gambus maestro) and his daughter, accessible at https://youtu.be/wEJMsTUhY9c. The research addresses two questions: (1) How is Ketepik Belian Padi in Gambus Belitung portrayed as a social identity? and (2) How is Ketepik Belian Padi in Gambus Belitung used as an element of social identity? The findings show that the identity of the people of East Belitung is deeply influenced by historical events and is preserved through these song lyrics.